Гибридная модель вставки постоянного тока; Энергия единой сети; № 2 (5) - Гусев А. С. Александр Сергеевич; Сулайманов А. О. Алмаз Омурзакович; Уфа Р. А. Руслан Александрович; Васильев А. С. Алексей Сергеевич; Лозинова Н. Г.; Суслова О. В. (2016, 2016)
Заглавие с экрана